Evaluation of Antimicrobial Interventions against E. coli O157:H7 on the Surface of Raw Beef to Reduce Bacterial Translocation during Blade Tenderization - Peter M. Muriana; Jackie Eager; Brent Wellings; Brad Morgan; Jacob Nelson; Kalpana Kushwaha (Foods, 2019)
The US Department of Agriculture, Food Safety Inspection Service (USDA-FSIS) considers mechanically-tenderized beef as “non-intact„ and a food safety concern because of the potential for translocation of surface Escherichia coli O157:H7 into the interior of the meat that may be cooked “rare or medium-rare„ and consumed. We evaluated 14 potential spray interventions on E. coli O157:H7-inoculated lean beef wafers (~106 CFU/cm2, n = 896) passing through a spray system (18 s dwell time, ~40 pounds per square inch, PSI) integrated into the front end of a Ross TC-700MC tenderizer. Inoculated and processed beef wafers were stomached with D/E neutralizing broth and plated immediately, or were held in refrigerated storage for 1-, 7-, or 14-days prior to microbial enumeration. Seven antimicrobials that showed better performance in preliminary screening on beef wafers were selected for further testing on beef subprimals in conjunction with blade tenderization. Boneless top sirloin beef subprimals were inoculated at ~2 × 104 CFU/cm2 with a four-strain cocktail of E. coli O157:H7 and passed once, lean side up, through an integrated spray system and blade tenderizer. Core samples obtained from each subprimal were examined for the presence/absence of E. coli O157:H7. The absence of E. coli O157:H7 in core samples correlated with the ability of the antimicrobials to reduce bacterial levels on the surface of beef prior to blade tenderization.